Oralidade e escrita: o jardim secreto da linguagem verbal na Educação Infantil - Soares, Silvana Mendes Sabino (2022)
Verbal language plays an important role in child development. In the oral modality, it organizes thinking and contributes to the understanding of the world around it, because it is through language that the child expresses his own way of perceiving how the process of interaction and cultural appropriation takes place cultural (VYGOTSKY, 1998). Living with speakers of a given language exposes them to a learning process that takes place in oral interaction. Speech becomes essential for life in society in which communication is the main means of interaction (BAKHTIN, 2011) and, especially in cultures that value and depend on written language, speech and vocabulary expansion are essential for an appropriation of the writing system. Orality as an object of teaching and learning, as the axis of verbal language must have equal value to reading and writing in the daily practices of Early Childhood Education, therefore, it can and should support the acquisition of writing in children. In this context, the thesis defended in this work is that the understanding of the relationship between orality and writing manifested in the pedagogical practices of preschool teachers can significantly help the child's process of acquiring writing. Therefore, the general objective was to investigate the relationship between orality and the acquisition of writing in pedagogical practices in the context of Early Childhood Education. Therefore, the following specific objectives were outlined: 1) To analyze the beliefs of Early Childhood Education teachers about the relationship between orality and the acquisition of writing; 2) Investigate the place of orality in the routines of preschool children in a public school in Fortaleza; 3) To analyze the articulation between the oral and written genres in the didactic actions of the professors; 4) Identify the teaching materials that favor the understanding of the relationship between orality and the acquisition of writing by children. The research was descriptive with a qualitative approach and involved a field study and document analysis. The techniques used were observation and semi-structured interviews with data recorded in a field diary, photographs and recording of speeches. Content Analysis was the methodology chosen to extract the categories of data constructed in the field and interpret the material, complemented with a triangulation between observation, interviews and document analysis. Piaget (1978; 2005), Vygotsky (2008) and Wallon (2007) theoretically support the acquisition and development of language in children. Vygotsky and Luria (2010), Bakthin (1992; 2010), Koch (2017) and Marcuschi (2005; 2010) constitute the framework that supports the studies of verbal language in the oral and written modalities. Ferreiro and Teberosky (1999), Melo (2014), Morais e Silva, (2011), Britto (2005), were relevant in the analyses of the writings derived from the relationship with orality. The results achieved point to a teaching practice that disregards a good part of the children's orality, even though there are moments in the routine of interactions called conversation circles and questions are asked to the children. The oral textual genres were little evidenced in the experiences proposed to the children and the spontaneous writing that shows, in fact, the constructed hypotheses had no space in the routine of propositions. The valued writing was copied from the blackboard, the one authorized by the teacher. We conclude that there is an urgent need to broaden the discussions about the orality and written relationship in order to guarantee the space of orality in daily teaching actions in Early Childhood Education in an intentionally planned way, aiming at the role of children. Our studies also point to the relevance of research that can enhance this discussion and give more visibility to the concepts and hypotheses that children formulate in the process of verbal language construction, keeping pedagogical work balanced with oral and written modalities.